Observation of Agricultural Business Conditions in RT 05 Parakan Jaya Village in Economic Terms During the Covid-19 Pandemic - Indah Sari, Mila; Sundarta, M. Imam (AMK : Abdi Masyarakat UIKA, 2023)
The world is currently going through difficult times due to the COVID-19 pandemic. Indonesia is also one of the countries affected by the COVID-19 pandemic. As a result of this pandemic, all human activities have been disrupted, even paralyzing the community's economic sector. The agricultural sector is a superior sector because the livelihood of the Indonesian population is mostly farming. Parakan Jaya village where most of the population as vegetable farmers. One of the vegetable producers in Bogor Regency. Vegetables are food crops as the basic needs of the community. This farming is carried out by ladies and gentlemen in the neighborhood of Rt 05 Rw 08 Parakan Jaya Village, Kemang Bogor. This service activity is called the independent written idea real work lecture (KKN-GTM) because the implementation technique is carried out independently and the location of the activity is carried out in the residential environment. The purpose of this service is to find out the activities of agricultural activities that are carried out every day, especially in the midst of the COVID-19 pandemic that is currently happening in Indonesia.